Comparative Study of Propeller Thrust Force on Unmanned Aerial Vehicle Using Ground Testing Methods and Theoretical Calculations - Afif Faishal; Imas Tri Setyadewi; Nur Aklis; Furqaan Harjanto; Ari Mukti Wibowo; Agung Supriyanto (Engineering Proceedings, 2025)
The propeller thrust force is a critical performance factor for UAVs, directly influencing the aircraft’s lift in the air. Various factors, such as propeller design, motor power, and operating conditions, influence thrust force. The propeller type also significantly impacts the thrust produced. It is essential to compare various types of propellers for UAV applications to obtain optimal thrust. This study employs ground testing and theoretical calculations to analyze and enhance propeller performance. Ground testing provides direct measurements of thrust force in controlled conditions, while theoretical study was conducted to predict thrust through mathematical calculations. This research was conducted on two different propellers, investigating variations in engine speed (Rpm). The results demonstrate that propellers A and B produce different amounts of thrust. These results were analyzed by comparing them with the outcomes of theoretical calculations. The experimental results and theoretical calculations show similar trends. However, there are noticeable differences in the thrust produced by both.